Aggregation and conformational stability evaluation of myoglobin in the presence of ionic surfactant - Mohammad A. Alsenaidy (Elsevier, 2018)
Sodium lauroyl sarcosinate (SLS) is frequently used for the solubilization of inclusion bodies in vitro due to its structural similarity to lipid plasma membrane. There are many factors that could influence protein aggregation propensity, including overall protein surface charge and hydrophobicity. Here, the aggregation pathway of myoglobin protein was studied under different conditions (pH 3.5 and 7.4) in the presence of varying concentrations of SLS to evaluate the underlying forces dictating protein aggregation. Data obtained from Rayleigh light scattering, ThT binding assay, and far-UV CD indicated that SLS have different effects on the protein depending on its concentration and environmental conditions. In the presence of low concentrations of SLS (0.05-0.1 mM), no aggregation was detected at both pH conditions tested. Whereas, as we reach higher SLS concentrations (0.5-10.0 mM), myoglobin started forming larger-sized aggregates at pH 3.5 and not pH 7.4. These results suggest that electrostatics interactions as well as hydrophobic forces play an important role in SLS-induced myoglobin aggregation. Keywords: Sodium lauroyl sarcosinate, Surfactant, Myoglobin, Protein aggregation, Amorphous aggregates, pH